2021
DOI: 10.1038/s41467-021-21928-4
|View full text |Cite
|
Sign up to set email alerts
|

Circulating mucosal-associated invariant T cells identify patients responding to anti-PD-1 therapy

Abstract: Immune checkpoint inhibitors are used for treating patients with metastatic melanoma. Since the response to treatment is variable, biomarkers are urgently needed to identify patients who may benefit from such therapy. Here, we combine single-cell RNA-sequencing and multiparameter flow cytometry to assess changes in circulating CD8+ T cells in 28 patients with metastatic melanoma starting anti-PD-1 therapy, followed for 6 months: 17 responded to therapy, whilst 11 did not. Proportions of activated and prolifera… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
37
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(44 citation statements)
references
References 53 publications
(66 reference statements)
3
37
0
Order By: Relevance
“…Moreover, circulating monocytes showed an important expression of immune checkpoints proteins (ICPs) with the characteristics of being inhibitory such as programmed death-1 (PD-1) and its ligand PD-L1 [ 23 ]. The expression and interaction of these molecules, which occurs in cases of exaggerated activation, blocks the effector action of T cells leading to the inhibition of immune response [ 27 ].…”
Section: Activation Of the Immune Response Driven By Sars-cov-2mentioning
confidence: 99%
“…Moreover, circulating monocytes showed an important expression of immune checkpoints proteins (ICPs) with the characteristics of being inhibitory such as programmed death-1 (PD-1) and its ligand PD-L1 [ 23 ]. The expression and interaction of these molecules, which occurs in cases of exaggerated activation, blocks the effector action of T cells leading to the inhibition of immune response [ 27 ].…”
Section: Activation Of the Immune Response Driven By Sars-cov-2mentioning
confidence: 99%
“…Another study in melanoma patients revealed a specific subset of T-cells correlated with ICI responders [94]. Twenty-eight patients with melanoma received anti-PD-1 ICI.…”
Section: Potential Biomarkers Of Clinical Response In Icimentioning
confidence: 98%
“…Other studies of squamous cell carcinoma (SCC) and basal cell carcinoma (BCC) observed that tumor-residing MAIT cells upregulated expression of IFN-γ, GZM K, GZM A and GZM M following PD-1 blockade [80]. Additionally, higher MAIT cell proportions were recently found to correlate with better responses to anti-PD-1 immunotherapy, with MAIT cells from responders having a greater cytotoxic function [28]. These results suggest that the PD-1 pathway may be involved in mediating MAIT cell dysfunction in certain cancers, and that, in addition to its canonical role in antitumor immunity, anti-PD-1 therapy may restore the expression of certain cytotoxic genes.…”
Section: Immunotherapymentioning
confidence: 98%
“…As such, the results should be interpreted with caution when assessing the applicability to humans. When MAIT cells were studied in melanoma patients on anti-PD-1 therapy, high MAIT cell proportions were found in those responding to PD-1 therapy as opposed to patients who were not responding [28] (Table 1). MAIT cells from responders also had higher levels MAIT cells in the melanoma lesions than non-responders, as well as increased levels of GZMB [28] (Table 1), indicating that MAIT cells from responders have higher cytotoxic functions while circulating and infiltrating the tumor site.…”
Section: Other Solid Tumorsmentioning
confidence: 99%